2021
DOI: 10.14201/eks.23921
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of a Group Counseling Program Based on Psychodrama in Enhancing Self-Awareness and Reducing Tension Among Tenth Grade Students in Qalqilia City

Abstract: This research was conducted through two studies, the purposes of the first study were to assess tension and self-awareness levels among the tenth-grade male and female students in Qalqilia city in Palestine, and to examine the impact of gender on tension and self-awareness. To achieve these goals a descriptive method was used, the sample consisted of (158) male and (152) female students age 16 years old. They were stratified randomly selected. This study found tension appears to be a broad problem in Palestine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…The third paper, titled The Efficiency of a Group Counseling Program Based on Psychodrama in Enhancing Self-Awareness and Reducing Tension Among Tenth Grade Students in Qalqilia City (Khalili & Swilem, 2021), aims to assess tension and self-awareness levels among tenth graders. The study revealed high rates of tension and low rates of self-awareness among the participants.…”
Section: Summary Of Contributionsmentioning
confidence: 99%
“…The third paper, titled The Efficiency of a Group Counseling Program Based on Psychodrama in Enhancing Self-Awareness and Reducing Tension Among Tenth Grade Students in Qalqilia City (Khalili & Swilem, 2021), aims to assess tension and self-awareness levels among tenth graders. The study revealed high rates of tension and low rates of self-awareness among the participants.…”
Section: Summary Of Contributionsmentioning
confidence: 99%